Zero-Click Search dan Answer Engines: Tinjauan Literatur Sistematis dalam Perspektif Pemasaran - Oscar Chrismadian Noventa (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The evolution of search technologies has led to the emergence of “zero-click search” and the transformation of search engines into “answer engines” that deliver direct answers without redirecting users to external websites. This shift carries significant implications for digital marketing strategies, particularly in brand visibility, search engine optimization (SEO), and performance measurement. This study presents a systematic literature review incorporating 30 sources from academic and industry publications (2020–2025) to explore the marketing implications and responses to this increasingly clickless search landscape. Key findings indicate that zero-click search has become a dominant norm, driven by the integration of generative AI that centralizes information within search result pages. Consequently, organic traffic is declining, prompting brands to adapt through strategies such as Answer Engine Optimization (AEO), content format diversification, and strengthening authority signals across digital channels. This review recommends a more holistic and evidence-based marketing approach to maintain brand relevance amid the ongoing disruption of digital search behavior.